Respuesta :

Esther

Answer:

C. 11

Step-by-step explanation:

Evaluate 2(x + 1) - 3 when x = 6.

2(x + 1) - 3 <== substitute 6 for x

2(6 + 1) - 3 <== distribute 2

2(6) + 2(1) - 3

12 + 2 - 3 <== add and subtract

14 - 3

11 <== answer

Hope this helps!

Hey there!

2(x + 1) - 3

= 2(6 + 1) - 3

= 2(7) - 3

= 14 - 3

= 11

OR

2(x + 1) - 3

= 2(6 + 1) - 3

= 2(6) + 2(1) - 3

= 12 + 2 - 3

= 14 - 3

= 11


Therefore, your answer is: 11


Good luck on your assignment & enjoy your day!



~Amphitrite1040:)